Allergen protein from mango (Mangifera indica) flowers pollen - Ranajit Kumar Shaha (2012)
Plant pollen is one of the most common causes of seasonal allergic disease world wide. In this study Mango flower pollen protein (MFPP) was extracted, filtered, fractioned, purified, and the homogeneity of this allergen protein demonstrated by the presence of a single band on SDS-PAGE. This purified protein showed the pectate lyase (Pel) activity expected of MFPP. The yield of MFPP was 4.10% of the total protein present in the aqueous extract of the pollen, while its allergenic activity was about 44% of the total dialyzable activity, as verified by blood tests. The molecular weight of the extracted protein, estimated by SDS-PAGE, was 27,000 Da and the isoelectric point of the extracted protein was 6.5. Application of this protein to mice produced a change in physical appearance and a rise in the levels of eosinophils and neutrophils level by 2%-5.5% and 34%-77.5%, respectively, relative to the normal levels. Hence the present study demonstrates that extracted protein from Mango flower pollen has allergic effects on animals.